1999
DOI: 10.4269/ajtmh.1999.61.898
|View full text |Cite
|
Sign up to set email alerts
|

Shipboard impact of a probable Norwalk virus outbreak from coastal Japan.

Abstract: Abstract. Norwalk virus has been implicated in shipboard diarrheal disease outbreaks throughout Asia. A large outbreak of suspected Norwalk virus was investigated on a U.S. Naval aircraft carrier following the clinical recognition of 450 cases of gastroenteritis over a 2-week period (September 14-28, 1997) during coastal exercises. A random sampling of 44 cases from 450 personnel who sought medical attention was compared with 19 controls. Junior enlisted sailors and marines comprised 97% of all cases. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Bacterial and viral agents having the potential to cause explosive and debilitating outbreaks may be as important, from a military perspective, because these agents cause the heavy burden of endemic disease. 43,53,54 In this respect, a study conducted among Israeli Defense Force troops during a routine deployment period found that, while sporadic cases of disease were caused by a number of different pathogens, most outbreaks were associated with Shigella, norovirus, and Salmonella. 55 Furthermore, impact of these agents with epidemic potential have been anecdotally described in a number of studies, including a study among United States Air Force personnel in this review that reported that onset of diarrheal illness in 5 of 222 airmen on 1 day had an adverse affect on operations, 36 and another study reported a flight mission was aborted mid-flight because of sudden onset of gastrointestinal illness in the pilot.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial and viral agents having the potential to cause explosive and debilitating outbreaks may be as important, from a military perspective, because these agents cause the heavy burden of endemic disease. 43,53,54 In this respect, a study conducted among Israeli Defense Force troops during a routine deployment period found that, while sporadic cases of disease were caused by a number of different pathogens, most outbreaks were associated with Shigella, norovirus, and Salmonella. 55 Furthermore, impact of these agents with epidemic potential have been anecdotally described in a number of studies, including a study among United States Air Force personnel in this review that reported that onset of diarrheal illness in 5 of 222 airmen on 1 day had an adverse affect on operations, 36 and another study reported a flight mission was aborted mid-flight because of sudden onset of gastrointestinal illness in the pilot.…”
Section: Discussionmentioning
confidence: 99%
“…AGE remains an unmet concern in military forces. Outbreaks due to NoVs infection have been reported in many countries, for instance, an outbreak involving 450 cases of AGE occurred on a US Naval aircraft carrier in 1997 [28]. AGE outbreaks have been reported in British [29], French [30], Singapore [31] and Chinese [32] military units.…”
Section: Population At Riskmentioning
confidence: 99%
“…Since then norovirus outbreaks in military personnel have regularly been reported in the literature (Table 3) [5,[16][17][18][19][20][21][22][23].…”
Section: Lessons From Outbreaksmentioning
confidence: 99%